Evaluating the efficacy of intragastric botulinum toxin a injections with two different quantities and sites for obesity - Tien-Yow Chuang; Cheng-Hung Chiu; I-Wen Penn; Cheng-Di Chiu (PLoS ONE, 2025)
Introduction Intragastric injections of botulinum toxin A (BTX-A) have shown promise in aiding weight reduction among obese patients, with a favorable safety profile and minimal adverse effects; however, the inconsistent results from prior studies highlight the need to examine key factors in the research of intragastric injection of botulinum toxin A, such as the dosage of BTX-A, the number and placement of injections. This study examines the efficacy of varying high doses, multi-gastric sites botulinum toxin A injections for weight control. Materials and Methods A total of 103 patients aged 18–65 with a BMI ≥ 25 kg/m² were assigned to four groups receiving endoscopic BTX-A injections at varying doses and sites: Group 1 (400 IU, fundus and body), Group 2 (300 IU, fundus and body), Group 3 (400 IU, antrum and body), and Group 4 (300 IU, antrum and body). Baseline comparisons used ANOVA, while a mixed model assessed the interaction among injection site, dose, and time on outcomes. Results Baseline measures showed no group differences in bodyweight, BMI, or body fat. The mixed model indicated significant reductions in bodyweight, BMI, and body fat with gastric fundus and body injections. Site and dose interactions significantly affected bodyweight (p = 0.024) and body fat (p = 0.041), but not BMI. Conclusions Endoscopic intragastric BTX-A injections effectively reduce body weight, BMI, and body fat, particularly with injections in the fundus and body regions.